2020
DOI: 10.3389/fonc.2020.00975
|View full text |Cite
|
Sign up to set email alerts
|

Porf-2 Inhibits Tumor Cell Migration Through the MMP-2/9 Signaling Pathway in Neuroblastoma and Glioma

Abstract: Tumor migration and invasion are key pathological processes that contribute to cell metastasis as well as treatment failure in patients with malignant tumors. However, the mechanisms governing tumor cell migration remain poorly understood. By analyzing the tumor-related database and tumor cell lines, we found that preoptic regulatory factor-2 (Porf-2) is downexpressed in both neuroblastoma and glioma. Using in vitro assays, our data demonstrated that the expression of Porf-2 inhibits tumor cell migration both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Matrix metalloproteinases (MMPs) play important roles in mediating angiogenesis, metastasis, and invasion. MMP-2/9 expression is related to the progression of many tumors, such as colon cancer ( 83 ), neuroblastoma ( 84 ), and bladder cancer ( 85 ). Paeoniflorin regulated miR-16/29b, which targeted MMP-9/2 ( 56 ) to inhibit the growth and invasion of multiple myeloma cells ( 57 ).…”
Section: Active Ingredients Of Chinese Medicine Targeting Mirna Inhibmentioning
confidence: 99%
“…Matrix metalloproteinases (MMPs) play important roles in mediating angiogenesis, metastasis, and invasion. MMP-2/9 expression is related to the progression of many tumors, such as colon cancer ( 83 ), neuroblastoma ( 84 ), and bladder cancer ( 85 ). Paeoniflorin regulated miR-16/29b, which targeted MMP-9/2 ( 56 ) to inhibit the growth and invasion of multiple myeloma cells ( 57 ).…”
Section: Active Ingredients Of Chinese Medicine Targeting Mirna Inhibmentioning
confidence: 99%
“…Overexpression of matrix metalloproteinases (MMP), paladin, and vimentin are linked to modified cell morphology and invasiveness in cancer cells [9][10][11]. MMPs increase the availability of growth factors and cytokines to receptor tyrosine kinases (RTKs) by degrading the extracellular matrix [12].…”
Section: Introductionmentioning
confidence: 99%
“…The hemopexin-like domain is critical for speci city during recognition and interacts with gelatin and collagen (Roeb et al 2002) About two decades ago, production of MMP9 by NB cells; its role in induced angiogenesis, tumor progression, and metastasis; and association of MMP9 with advanced disease stage and poor clinical outcomes were documented (Sugiura et al 1998;Ribatti et al 1998;Ara et al 1998). Since then, a growing number of studies have reiterated the role of MMP9 in NB progression and poor clinical outcomes with the recognition of mechanisms and cellular functions involved (Li et al 2020;Sans-Fons et al 2010;Cheng et al 2005). Consistently, global efforts were focused on identifying lead therapeutic deliverables that could target activated MMP9 signaling in NB (Li et al 2020;Xu et al 2019;Farabegoli et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Since then, a growing number of studies have reiterated the role of MMP9 in NB progression and poor clinical outcomes with the recognition of mechanisms and cellular functions involved (Li et al 2020;Sans-Fons et al 2010;Cheng et al 2005). Consistently, global efforts were focused on identifying lead therapeutic deliverables that could target activated MMP9 signaling in NB (Li et al 2020;Xu et al 2019;Farabegoli et al 2018). Conversely, studies from our lab and others have showed therapeutic pressure-associated acquired molecular rearrangements, clonal selection, and cellular function, leading to drug resistance, NB evolution, and poor outcomes (Somasundaram et al 2019;Aravindan et al 2013b).…”
Section: Introductionmentioning
confidence: 99%